Reviews of new publications - Lambert, Frank (KUKILA, 2009)
Handbook of the Birds of the World. Volume 11: Old World Flycatchers to Old World Warblers. del Hoyo, J., A. Elliott & D. Christie (eds). Lynx Edicions Handbook of the Birds of the World. Volume 12: Picathartes to Tits and Chickadees. del Hoyo, J., A. Elliott & D.A. Christie (eds). Lynx Edicions